The sea of disappointment : Thomas Kinsella's pursuit of the real - Fitzsimons, Andrew Joseph (Trinity College (Dublin, Ireland). School of English, 2005)
This study provides an extensive examination of the work of Thomas Kinsella by addressing the fundamental question of form which his poetry presents. There are two phases in Kinsella’s writing: one contains poems written for the most part in conventional stanzaic forms; the other utilises forms less bounded by inherited formal convention. Discussions of Kinsella acknowledge the fact of the formal change, and explore how this is manifested in the poems, yet so far no discussion has provided a reading of the underlying impulse that would account for the transformations in the work. This thesis shows why Kinsella questioned the formal procedures of the poetry, and establishes the fundamental drive behind his poetic activity as the pursuit of the Real.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin